2021
DOI: 10.3389/fphar.2021.652074
|View full text |Cite
|
Sign up to set email alerts
|

Two Worlds Colliding: The Interplay Between Natural Compounds and Non-Coding Transcripts in Cancer Therapy

Abstract: Cancer is a devastating disease and has recently become the leading cause of death in western countries, representing an immense public health burden. When it comes to cancer treatment, chemotherapy is one of the main pillars, especially for advanced stage tumors. Over the years, natural compounds have emerged as one of the most valuable resources for new chemotherapies. It is estimated that more than half of the currently used chemotherapeutic agents are derived from natural compounds. Usually, natural compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 294 publications
(315 reference statements)
0
3
0
Order By: Relevance
“…Various classes of bioactives were shown to exert anticancer effects through the downregulation of microRNAs, most often oncomiRs, and the release of mRNAs coding for antiproliferative proteins. The review by Sabo [ 152 ] and that by Cherng [ 153 ] showed the relationship between natural compounds and nc-RNAs in cancer cells, and the potential use of their bioactives in cancer therapies. Xu and colleagues described, for the first time, the involvement of pinene, one component of LEO, in the upregulation of p27/CDKN1B, a cell cycle-blocking protein, through the downregulation of miR-221 [ 153 ].…”
Section: Leo Therapeuticsmentioning
confidence: 99%
“…Various classes of bioactives were shown to exert anticancer effects through the downregulation of microRNAs, most often oncomiRs, and the release of mRNAs coding for antiproliferative proteins. The review by Sabo [ 152 ] and that by Cherng [ 153 ] showed the relationship between natural compounds and nc-RNAs in cancer cells, and the potential use of their bioactives in cancer therapies. Xu and colleagues described, for the first time, the involvement of pinene, one component of LEO, in the upregulation of p27/CDKN1B, a cell cycle-blocking protein, through the downregulation of miR-221 [ 153 ].…”
Section: Leo Therapeuticsmentioning
confidence: 99%
“…Emerging evidence, mainly in the context of cancer research, suggests that the expression of ncRNAs, as well as their downstream targets, can be modulated by the intake of specific nutrients and natural compounds ( Ferrero et al, 2021 ; Scoditti et al, 2021 ). For instance, natural products such as curcumin, resveratrol, and epigallocatechin-3-gallate, have been shown to exhibit anti-cancer effects by modulating the expression and the function of several ncRNAs, with consequent inhibition of cancer cell growth, induction of apoptosis, and increased therapeutic efficacy of conventional cancer therapy ( Zhang B. et al, 2020 ; Sabo et al, 2021 ). Within the above mentioned natural compounds, resveratrol (3, 5, 4′-trihydroxystilbene), a nonflavonoid polyphenol contained in various foods, e.g., grapes, apples, blueberries, cocoa and peanuts, has been extensively studied in view of its numerous biological effects ( Galiniak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many studies have demonstrated that the development pathogenesis of colorectal cancer is highly influenced by ncRNAs [ 10 ], the abnormal expression of oncogenic and tumor-suppressor molecules, and the abnormal activation of various cell signaling pathways [ 11 , 12 ]. In recent years, some important natural compounds, such as phenolics, terpenoids, and meroterpenoids, have been confirmed to have anticancer effects by regulating the expression and function of ncRNAs [ 13 ]. Particularly, naturally derived polyphenols have been safely used for many years and have shown real potential for therapeutic effects in most cancers through the regulation of miRNAs and lncRNAs [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%